Measuring the Level of Dimensions of the State of Competition Anxiety ( the State of Cognitive and Physical Anxiety and Self-Confidence ) of the Players of Some Clubs in Nineveh - Ahmed Ahmed (College of Physical Education and Sport Sciences, 2021)
The aim of the research is to: -  Measuring the differences in the dimensions of the competition anxiety stat scale, the state of cognitive and physical anxiety and self-confidence for the research sample in advanced football. The researchers found that : -  that the level of dimensions in the case of competition anxiety is a state of cognitive and physical anxiety and self-confidence among the players of the Fatwa Club, and it was better than that of the players of Al-Baladiya and Al-Waves Club. The researchers recommended that  : - Paying attention to the training units that grow and develop in the level of dimensions of the state of competition anxiety, the state of cognitive and physical anxiety and self-confidence of the players of the municipality club and sports waves in football .